India-China Relations in the Context of the Tibet Issue: A Study : भारत चीन संबंध तिब्बत समस्या के परिप्रेक्ष्य में एक अध्ययन - Seema (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
India emerged as a democratic republic on August 15, 1947, gaining independence from colonial rule. Similarly, China emerged as a communist nation on October 10, 1949. Since both nations share a common border, Tibet was designated as a buffer state between the two countries during the colonial era. Several factors influence the relationship between these two states, but the issue of Tibet is the primary factor affecting their ties. Abstract in Hindi Language: भारत 15 अगस्त 1947 को भारत लोकतांत्रिक गणराज्य के रूप में औपनिवेषिक शासन से स्वतंत्र होकर उदय हुआ। इसी प्रकार चीन 10 अक्टूबर 1949 को एक साम्यवादी राष्ट्र के रूप में उदित हुआ चूंकि दोनों ही राज्यों की सीमा आपस में जुडी हुई है। औपनिवेषिक शासन काल में तिब्बत को दोनों राज्यों के मध्य बफर स्टेट के रूप में निर्धारित किया गया। दोनों राज्यों के संबंधों को अनेक तथ्य प्रभावित करते हैं परंतु तिब्बत की समस्या मुख्य तथ्य है जो इसे प्रभावित करता है। Keywords: भारत, बफर स्टेट, लोकतांत्रिक, साम्यवादी, गणराज्य औपनिवेषिक, शासन, स्वतंत्र, तिब्बत, प्रभावित